Luc Reychler: A Pioneer in Sustainable Peacebuilding Architecture - Reychler, Luc; Langer, Arnim (Pioneers in Arts, Humanities, Science, Engineering, Practice, 2020)
XVIII, 357 p. 54 illus., 23 illus. in color.